Site diversity against rain fading in LMDS systems - Shamsan Abdo, Zaid Ahmed (2007)
Local Multipoint Distribution Service (LMDS) is a new terrestrial fixed radio technology for broadband communication applicable that can be used to provide digital two-way voice, data, Internet, and video services or other digital services requiring high capacity traffic channels. LMDS is a point to multipoint wireless system operating at frequencies above 20 GHz, the most serious impairment at these frequencies is rain fading. In the system point of view a moving rain cell over the LMDS service area will not only attenuate the desired signal but also the interferer. Many techniques could be used to overcome rain fading. Applying Site Diversity as a possible solution to reduce the effect of rain is necessary, because a rain-cell degrades the system performance at a part of the service area but the rain can improve the carrier signal conditions elsewhere depending on the locations of the Base Station, Terminal Station and the rain-cell. The rain attenuation of different locations in Malaysia region in a given LMDS is calculated and the effects of a moving rain cell over an LMDS system are analyzed, different situations of interference according to the position of the rain-cell over the service area of LMDS are elaborated. The site diversity is implemented based on the ITU-R Recommendations to enhancement LMDS. The location dependent C/I in the LMDS service area under rainy conditions with and without site diversity technique is calculated and simulated. Different cell sizes of LMDS with and without site diversity are considered in this project for significant analyses and discussions. It is found that site diversity has high ability to improve the performance level of all LMDS service area specially under rainy conditions.